Pengembangan E-Modul Berbasis Social Scientific Issue (Ssi) Untuk Meningkatkan Kemampuan Berpikir Kritis Dan Enviromental Care Pada Materi Kimia Hijau Di Kelas X SMA Dengan Menggunakan Aplikasi Fliphtml5 - Hadilah Rasyih; Asmadi M. Noer; Rasmiwetti Rasmiwetti (Postgraduate, University of Mataram, 2024)
This research aims to develop a valid and reliable e-Module based on socio-scientific issues in green chemistry and to evaluate its impact on students' environmental care and critical thinking skills. The Research and Development (R&D) method was employed using the ADDIE model, which includes five phases: analysis, design, development, implementation, and evaluation. Data were collected through interviews, student questionnaires, validation sheets, and user response questionnaires. Small-scale trials were conducted via one-on-one tests and user response assessments, involving three students with varying abilities, three teachers, and 30 students from SMAN 2 Siak Hulu, SMAN 2 Tambang, and SMAN 1 Bangkinang Kota. The e-Module received validation ratings of 92% from material experts and 99% from media experts, classifying it as highly valid. The one-on-one test provided feedback for improving certain e-Module components. User responses were highly positive, with teachers giving a 92.1% rating and students 96.6%. The paired t-test revealed a significant improvement in environmental care and critical thinking skills, with the experimental group achieving a high N-Gain value of 0.71, while the control group reached a medium category with an N-Gain of 0.42.